Design of a novel punch planter capable of producing equidistant seed spacing of irregular shaped seeds - De Resende, Ricardo Capucio (Cranfield University, 2002)
Plants uniformly spaced in the field have a more efficient use of resources, due to their even distribution. There are also a better ability to compete against weeds, less spread of disease and lodging. Consequently the yield should be improved. Precise seed placement and seed location in the field are important for the management of the crop at a plant-scale level, for such operations as mechanical weeding or herbicides applications. A novel concept of a precision drill was developed to achieve an advanced control of seed placement and location in the soil. The fundamental principle adopted, was to trap seeds inside holes in the soil, to eliminate seed bounce and roll in the furrow. The concept is simple and consists of only three moving parts, two punch wheels and a fen, to precisely place the seeds in the soil. A rotary punch planter prototype was designed and built, including a vacuum operated seed metering unit and an air delivery system. The prototype was tested under laboratory conditions to determine its performance in relation to seed placement, when planting wheat and pelleted sugar beet seeds. The experiments were done in a soil bin at 4, 6 and 8 km/h Seed spacing and depth were set to 18 cm and 3 cm, respectively. The results show that, once a seed had been successfully selected the prototype had the ability to precisely place seeds in the soil for wheat and sugar beet seeds, at all speeds tested. The grand mean for precision was 12.2%. The CP3 value for wheat and sugar beet at 8 km/h were 26.2 % and 60.8 %, respectively. The main problems encountered were seed selection at higher speeds, and incorrect seed transfers from the seed metering unit to the delivery punches, which occurred for both seeds at all speeds. The concept has proved to be effective and modifications of the seed metering mechanism to improve its performance is recommended to further improve upon the concept.